Ecology and management of the leafhopper vectors (Cicadulina Spp.) of maize streak virus - Van Rensburg, George Diederick Janse (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1990.